INTRODUCTION TO THE SPECIAL ISSUE SPOTLIGHTING PAPERS FROM THE AERA SPECIAL INTEREST GROUP ON ONLINE TEACHING AND LEARNING - Swan, Karen; Richardson, Jennifer (Online Learning, 2017)
The American Educational Research Association (AERA) is the premier association of educational research professionals. AERA supports 12 divisions and 150 Special Interest Groups (SIGs). One of the latter is the Special Interest Group on Online Teaching and Learning (SIG-OTL). SIG-OTL is a multi- disciplinary community of scholars focused on the creation, use, and evaluation of online learning environments. This special issue spotlights 11 papers taken from those presented at the 2017 annual meeting.